MEDIEVAL MATCHING MARKETS - Lars Boerner; Daniel Quint (International Economic Review, 2022)
We study the regulation of brokerage in wholesale markets in premodern Central Western Europe. Examining 1,804 sets of rules from 82 cities, we find brokerage was primarily a centralized matchmaking mechanism. Brokerage was more common in towns with larger populations, better access to sea ports and trade routes, and greater political autonomy. Brokers' fee structures varied systematically: price-based fees were more common for highly heterogeneous goods, quantity-based fees for more homogeneous goods. We show theoretically that this was broadly consistent with total surplus maximization, and that brokerage was more valuable in markets with unequal numbers of buyers and~sellers.
Keywords: 330